Assessment of Psychological Impact and Complications In Post-Coronavirus Disease Patients - Dr. Pradeep Kumar Challa; Kamreddy Sushma; Emmadi Akhila; Gudepu Ashok Kumar; Katta Pavan Kumar (International Journal of Pharma and Bio Sciences, 2022)
Coronavirus disease (COVID-19) is caused by SARS-COV2, which denotes the causative agent of a potentially lethal disease that is of great global public health concern. Although most of the COVID-19 patients get better and return to their normal health, only a few patients have symptoms that can last for weeks or even months’ later recovery from acute illness. Post COVID complications are deteriorating the health-related quality of life of the survivors, thereby making their condition worse. The main aim of this study is to assess the impact and the complications of the COVID-19. The objectives of the study are to know the extent of the long-term complications affects the quality of life of the COVID-19 cured subjects and to assess the impact of post-covid complications on the physical health of the COVID survivors. It is a hospital-based retro-prospective study involving 210 subjects. The data was collected by using the patient interviews, laboratory reports and by the questionnaire developed. Data was analyzed by using the GraphPad Prism 9.1.2(226) software. In our study of 210 patients about 77% were using the nutritional supplements after the COVID-19 recovery. Most of them were using nutritional supplements to overcome the fatigue caused by the COVID attack. It was observed that 52% of subjects were depressed during the covid attack.